DETERMINATION OF THE PHYTOCHEMICAL CONSTITUENTS AND THE ANTIBACTERIAL ACTIVITY OF THE ROOT BARK EXTRACT OF NEOCARYA MACROPHYLLA (SABINE) PRANCE, AGAINST KLEBSIELLA PNEUMONIAE, AN EAR INFECTION-CAUSING PATHOGEN (FUDMA JOURNAL OF SCIENCES, 2020)
Neocarya macrophylla root bark extractis a potential source of novel antimicrobial compounds, especially against Klebsiella pneumoniae, a bacterial pathogens. N. macrophylla is a medicinal plant commonly used in traditional medicine in Northern Nigeria to treat asthma, skin infections, treatment of wounds, pulmonary troubles, dysentery, inflammations and it is also used for the treatment of eye and ear infections.The susceptibility test results showed inhibition range of 15, 13, 11, 13 and 14mm for the NM, NM4, NM3, NM2 and NM1 respectively against test organism at 50mg/mL, and 09, 11, 09, 12 and 13mm for NM, NM4, NM3, NM2 and NM1 respectively at 25mg/mL, and finally -, 09, -, 09 and 09mm for NM, NM4, NM3, NM2 and NM1 respectively at 12.5mg/mL. This indicates NM, NM1, NM2 and NM4 to be the most active fractions against the organism at 50mg/mL in a respective manner and the least active fraction is NM3 at 25mg/mL, while fractions NM1, NM2 and NM4 showed no activity at 12.5mg/mL against the test organism. The test results indicated that root back extract of N. macrophylla has antibacterial potency and could be used as an alternative antimicrobial therapy
Keywords: Neocarya macrophylla, Klebsiella pneumoniae, Phytochemicals, Antibacteria